Produção de plásticos biodegradáveis à base de queratina extraída de penas de frango por rotas verdes - Vanderlei, Rafael Marques (Universidade Federal de São Carlos, 2023)
Chicken feather is a by-product widely generated by the poultry agroindustry. However, its large-scale production and the challenges associated with waste management raise substantial concerns about its environmental impacts. Chicken feathers are predominantly composed of keratin, a protein that can be potentially valued towards new biodegradable materials with desirable physical properties for various applications. Focusing on this major objective, in this doctoral thesis, keratin was extracted from industrial chicken feather waste through sulfitolysis, followed by recovery using various precipitating agents: HCl, citric acid, NaCl, and acetone. This approach enabled the extraction of keratin in a dialysis-free, fast, and scalable way, using low-cost and non-toxic reagents, with emphasis on the acetone precipitation for which a recovery yield of 80% was obtained. Life cycle assessment outlined the main environmental hotspots in the keratin production, and a circular economy concept was studied to mitigate its environmental impacts. Chemical analysis revealed that the disulfide bonds present in keratin were converted into S-sulfocysteine, facilitating the keratin processing by thermo-molding. Transparent and water-insoluble thermoplastic films were produced with desirable properties for packaging applications, for example. The precipitating agents had direct implications on the distribution of molar mass, morphology, and hydrophobicity of the keratin films. These characteristics allowed obtaining films with a range of mechanical properties, from rigid films, with an elastic modulus above 400 MPa, to films with elongation at break as larger as 70%, for a tensile strength around 10 MPa. This thesis shows the potential for valuing chicken feather waste in the development of biodegradable keratin-based materials with reduced environmental footprints.
Production of biodegradable plastics based on keratin extracted from chicken feathers by green routes
Keywords: Avaliação de ciclo de vida; Filme biodegradável; Precipitação; Queratina; Termo-prensagem; Biodegradable film; Compression molding; Keratin; Life cycle assessment; Precipitation; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS